Development and Pilot Evaluation of an Instructional Model Integrating Metacognition Theory and Collaborative Learning for English Writing Instruction among Chinese Non-English Major Undergraduates - Zhao, Xueting; Wanpen, Supratra; Kaewmanee, Theerapong (Journal of Multidisciplinary in Humanities and Social Sciences, 2026)
This study aimed to: 1) develop an instructional model integrating Metacognition Theory and the Collaborative Learning Approach to support English writing instruction for non-English major undergraduates in China, and 2) conduct a pilot evaluation of the developed instructional model based on expert evaluation and supporting evidence from pilot implementation. The model, structured across Pre-Writing, While-Writing, and Post-Writing phases, was implemented over a two-week intervention with 50 first-year non-English majors who were enrolled in the first semester of 2025 at a Chinese university, selected via purposive sampling. A one-group pre-test/post-test design was employed. Data were collected through expert evaluation forms and English writing tests, analyzed using descriptive statistics and a paired-samples t-test. The research results are as follows: 1) Expert validation confirmed the model’s high appropriateness (M = 4.47, SD = 0.76). 2) The pilot implementation demonstrated a statistically significant improvement in students’ writing performance, with post-test scores (M = 68.7, SD = 8.2) surpassing pre-test scores (M = 62.3, SD = 9.5), t (49) = 5.80, p < .001. Pedagogically, the model fostered enhanced self-regulated learning, evidenced by more systematic planning, ongoing self-monitoring, and reflective revision, facilitated through structured peer interaction. The findings provide preliminary evidence that the integrated model, by cultivating metacognitive strategies and collaborative engagement, can enhance English writing ability, offering a promising alternative to traditional instructional practices.